Analysis of Students’ Motivation in Learning English at STISNU Aceh - Tgk Lina Rahmalia (Intelektualita, 2021)
The problems of the research concerned with the university students’ motivation in learning English. The study would like to find out the kinds of motivations they have and which kinds of motivation dominate them; integrative or instrumental motivation. The respondents of this study were sixty students of university student at Stisnu and nearby who enrolled in English Education Study Program in academic year 2018-2019.This study used quantitative as well as descriptive method and is designed to find out some information from actual condition. Then, a set of questions or questionnaire was used to collect the data and then analyzed and computed the answers of the respondents to find out the value and mean value of each kind of motivation.Based on the result of the study, the researcher found that most of the students have little motivation in learning English. They tend to have instrumental motivation. They have enough self-confidence in understanding oral communication, reading, writing, and speaking but the aspect of culture is less exposed in English language learning. The teachers of English should use the students’ own motives for joining the course, encourage students to be active in the class by giving chance to suggest or giving opinion to solve problems in an experiment activity for instance, ask the students what type of teaching and learning which motivate them most and what kinds of classes which are not motivated them, encourage students to focus on their improvement not only grade or examination. The students can do self-assessment of their own work and find out their strength and weaknesses, encourage the students to work cooperatively in groups without pressure, give feedback without judging their mistakes and errors. Then, give reward which can establish their self-confidence and competence later